Natural Enemies Acquire More Prey Aphids from Hormone-Treated Insect-Attracting Plants - Xiaosheng Jiang; Xingrui Zhang; Guodong Han; Shovon Chandra Sarkar; Feng Ge (Plants)
Exogenous plant hormones regulate the agronomic and physiological performance of plants and thus can influence the abundance of insect groups. We surveyed the arthropods on flowering plants Cnidium monnieri and found that the abundance of natural enemies Propylaea japonica and Orius minutus in the plots treated with salicylic acid (SA) and indole acetic acid (IAA) was significantly increased compared with those in the clean water (control) plots. Then, we investigated the effects of spraying SA, IAA, and clean water on the population parameters of Semiaphis heraclei reared on C. monnieri. Our results from the age-stage, two-sex life table analysis revealed a significantly shorter pre-adult duration for aphids reared on SA-treated C. monnieri compared to those reared on the other two treatments. The intrinsic rate of increase, finite rate of increase, and net reproductive rate of aphids reared on SA- and IAA-treated C. monnieri were significantly higher than those of aphids reared on clean water-treated C. monnieri. The fecundity rate was higher under the SA and IAA treatments than in the control, but the difference was not significant. This improved the ability of flowering plants to attract natural enemies by providing a larger food source.